ERA Forum Journal of the Academy of European Law - Heusel, Wolfgang; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
ERA Forum is a quarterly legal journal published by the Academy of European Law as part of its mission to raise understanding and promote good practice of European law. It is aimed at practitioners, including lawyers in private practice, in-house counsel, judges, prosecutors and civil servants. Published articles are drawn primarily from the most outstanding presentations delivered at ERA's conferences. This special feature provides a "market test", guaranteeing the journal's quality and relevance to the practitioner. The focus of the journal is European law, within which distinct sub-areas of law are highlighted either by selecting one or more thematic focal points for a regular issue or by publishing special issues. The journal is thoroughly European, from the composition of its editorial and advisory boards through the selection of its contributors. Most articles are published in English, but articles in French and German are included. Officially cited as: ERA Forum.
Keywords: Political science; Public international law; European Economic Community literature; Public International Law; European Integration; Political Science